The Influence of Information Technology on Student’s Behavioural Nature in the Class Room - Ali, Liaqat (Asian Journal of Education and Training, 2018)
The use of mobile phones and other gadgets in the university class room is becoming a culture in the modern age of technology. Some students use this technology for the purpose of information only. However, it was noted that others use mobile phone to receive messages through different applications such as WhatsApp, Facebook, Instagram and Viber. It is therefore important to understand the impacts of their behaviour. On the other hand, the use of mobile technology effects the teaching strategies. Teachers need to adopt new teaching methodologies to make sure that educational objectives and student’s deep learning could be achieved together. It is therefore critical to adopt a balance approach. The research in this paper conducted a survey to find the relationship between student’s behaviour and the use of mobile technology. The analysed data is used to balance the approach and to achieve educational objectives.